Introduction: The spatial turn in social theory - Blank, Yishai; Rosen-Zvi, Pnina (Hagar: Studies in Society and Culture, 2010)
[...] theoreticians writing soon after 1968, such as Lefebvre and de Certeau, saw space as at least having the potential to liberate the human subject from the grips of the oppressive state. [...] it was the "infiltration" of other disciplines that discovered space into the architectural discourse which marked the tum in architecture.